The Holders of the "Word of Truth" The Pharisees in Pseudo-Clementine Recognitions 1.27-71 - Bourgel, Jonathan 1979- (2017)
There is general scholarly agreement that Recognitions 1.27-71 constitutes a discrete literary unit based on a Jewish-Christian document from the mid-to late second century c.e., originating in Judaea or its environs. This passage gives an account of history from the creation of the world through the seventh year after Jesus's crucifixion, when James the Bishop of Jerusalem and the disciples hold a disputation with the Jewish sects in the Temple. Recognitions 1.27-71 has several remarkable characteristics such as a fierce opposition to sacrifices and a deep anti-Paulinism. The present paper investigates another feature of this account rarely addressed in modern scholarship, namely, its singular treatment of the Pharisees. As we shall see, the depiction of the Pharisaic movement in this text is relatively positive, which is most uncommon in early Christian literature. This article explores not only the representation of the Pharisees itself, but also several apparent analogies between Recognitions and rabbinic tradition. It should provide new insights, not only for the group in which this text originated, but also on the relations of the group with the rabbinic movement.